(untitled) (Global Journal of Science Frontier Research, 2025)
This paper proposes that the Charge Neutralization Process CNP represents a fundamental physical principle underlying stability emergence and creativity in both the physical and biological realms Rather than viewing charge neutralization as a passive consequence of electrostatic interaction this work frames it as a primary driver of order and complexity in nature From atomic structures to neuronal systems CNP provides a dynamic mechanism by which the universe balances oppositional forces enabling the formation of stable systems and novel structures